Feasibility and the care-full just city: Overlaps and contrasts in the views of people with disability and local government officers on social inclusion. (May 2020) - Rachele, Jerome N.; Wiesel, Ilan; van Holstein, Ellen; Feretopoulos, Vickie; de Vries, Tessa; Green, Celia; Bicknell, Ellen
Abstract: In this paper we consider how 'feasibility' considerations in urban policymaking fit within wider theories of the care-full just city. Specifically, we consider practical ways to bring together what people with disability consider the most important initiatives to enhance their social inclusion in the city, and the perceptions of local government officers about what initiatives are feasible to implement in the context of complex urban governance structures. While feasibility and care-full justice might appear incompatible, we argue that notions of responsibility, competence, resourcing and action are all integral to both 'feasibility' and the care-full just city. This discussion is informed by empirical data from a research project undertaken in the City of Melbourne, Australia, following a mixed-method approach called group concept mapping. We organised a series of structured workshops with people with physical and mobility, sensory, intellectual, and psychosocial disabilities, and with government staff, disability advocates, and academics to collect ideas on how to enhance social inclusion for people with disability in the City of Melbourne, and to rate the importance and feasibility of those ideas. Highlights: Disability inclusion in the city was examined using group concept mapping. Data was collected from people with disability and government staff. 240 ideas to improve disability inclusion were devised. Concepts of importance and feasibility of implementation are discussed.